Counseling students’ experiences viewing virtual reality case studies - Tyler Wilkinson; Kathleen Bazile (Teaching and Supervision in Counseling, 2019)
Virtual reality is a technological medium that provides a three-dimensional interactive environment where individuals become immersed and, in some cases, can manipulate the environment. This technology shows promise in its application with simulated educational experiences. Most of the application in the literature has been with medical training programs that have attempted to use virtual reality for simulated patient-medical professional interactions. Research is lacking on the potential application of virtual reality with counselor training. We applied virtual reality technology with counseling students at different points in their training program where they were exposed to virtual counseling situations. The participants of this phenomenological study indicated that simulated counseling situations felt more authentic than traditional role-plays and encouraged its use early in counselor training programs. Future applicability in counselor training, limitations, and research recommendations are discussed
Keywords: simulated education; counselor training; virtual reality